Leveraging Local Community Capacities for Sustainable Security: A Case Study of the Border Villages in Darmiyan and Sarbisheh Counties - Javad Mikaniki (برنامه ریزی فضایی)
AbstractBackground: The sustainable security of rural settlements is a topic that has been studied from various perspectives by using different approaches. Purpose: This article explored an integration-oriented approach to reveal the capacities of the local community in achieving sustainable security in the rural border settlements of Darmiyan and Sarbisheh Counties in Southern Khorasan. Research Method: The study employed a quantitative, descriptive-analytical research method with a survey approach. The statistical population consisted of 62 rural settlements within 30 kilometers of the common border with Afghanistan, comprising 4,502 households. A non-probability method was used for sampling at the village level, while a random-stratified probability method was employed at the household level. The sample size was 354 rural households, which was calculated using Cochran's formula. The data collection tool was a researcher-made questionnaire examining variables related to participation, trust, cohesion, and social solidarity. Findings: The results indicated that the components of participation, trust, and social solidarity had a significant impact on sustainable security from the local community's perspective. Furthermore, the research confirmed a favorable mentality towards social components in rural areas, which could foster the growth and development of security and its dissemination to weaker rural areas. Keywords: Sustainable Security, Social Participation, Social Trust, Social Cohesion. IntroductionA rural community refers to a set of human behaviors and interactions that take place in villages. The fundamental characteristics of rural society can be examined from an economic and social perspective. Economically, rural areas typically rely on a subsistence-based economy dependent on the agricultural sector. Socially, they are often marked by cooperation, mutual assistance, homogeneity, and cultural unity. The settlement patterns in rural areas are influenced by natural, economic, and social factors. Social institutions are relatively stable patterns of behavior or a set of relationships, trends, and tools that are built around social interests and needs. Investigating and analyzing the capacities of rural societies, especially in border areas, based on their economic and social characteristics are of particular importance. South Khorasan Province shares a 331-kilometer border with Afghanistan, spanning the counties of Nahbandan, Sarbisheh, Darmiyan, and Zirkoh. This border region has long been considered one of the safest in the country's east and southeast. The purpose of this research was to identify the capacities of the local community in the border settlements of Sarbisheh and Darmiyan Counties, particularly in terms of social activities, such as participation and social cohesion, as well as cultural institutions. Materials & MethodsThis research employed a descriptive-analytical approach and was considered an applied research. The required data were collected using both library research and a survey method. The primary data collection tool was a researcher-made questionnaire, which was administered after establishing its validity and reliability among the research sample population. The main components of the research included collaborative capacities, social trust, cohesion, and social solidarity, which were measured through 33 Likert-scale items (5 options). The collected survey data were analyzed using both descriptive (central tendency and dispersion indices) and inferential statistics. Due to the non-normal distribution of the data, the research hypotheses were tested using the binomial test. The statistical population consisted of the villages located in the Gezik and Tabas sections of Darmiyan County (33 villages) and the villages in the Doroh and Lano sections of Sarbisheh County (65 villages). Sampling was conducted at two levels: first, the villages within 30 kilometers of the common border with Afghanistan were included, totaling 62 villages; then, at the household level, a simple random probability sampling method was utilized. Research FindingsThe area studied in this research included the border villages of Darmiyan and Sarbisheh Counties in South Khorasan Province. Darmiyan City is located between 32°33' and 33°21' north latitude and 59°28' and 60°41' east longitude. Sarbisheh City, on the other hand, is situated between 32°02' and 32°56' north latitude and 59°13' and 60°53' east longitude. Darmiyan comprises 4 districts, 4 cities, and 3 villages, covering an area of 5,816 m2. Sarbisheh, with 3 districts, 3 cities, and 6 villages, spans an area of 7,928 m2 and shares a border with Afghanistan. This research focused on the border settlements located within the border districts and villages of these two cities. The research findings indicated that the component of people's participation in solving rural problems had the highest average score of 4.29 among the variables examined. From the perspective of the majority of respondents, the cooperative spirit of villagers had a highly influential role in achieving sustainable security. Additionally, the will and collective awareness in solving problems were also considered important, ranking in the second or third highest categories. Since the average for the other variables was higher than 3 (the midpoint), it could be concluded that the majority of respondents perceived the impacts of all variables on realizing stable security to be above average. Regarding social trust, the trust of family members in each other scored the highest with an average of 4.2. This was followed by trust in relatives and friends, while trust in official and government organizations ranked the lowest. However, as the average for all social trust variables exceeded 3, it could be said that from the perspective of the local community, social trust, particularly within family, friends, and neighbors, was seen as effective in realizing sustainable security. The research examined the impact of cohesion and solidarity on the realization of sustainable security from the perspective of the local community. The findings indicated that the variables of family relationships and ties, religious and ideological convergence, and interaction with each other scored above 4 (on a high scale), suggesting a relatively high level of internal convergence within the local community in the border settlements. While political and party solidarity had the lowest average among the variables, the average for all variables was still above 3.5, indicating that the different aspects of cohesion and solidarity were seen as contributing to sustainable security in the studied area.Hypothesis 1: Collaborative capacities in the studied area have been highly effective in achieving sustainable security.The observed ratio in the second group was much higher than the first group and the p-value supported the researcher's hypothesis that the participation capacities within the rural community had been highly effective in achieving sustainable security.Hypothesis 2: Social trust in the study area has been highly effective in achieving stable security.The observed ratio in the second group was much higher than the first group and the p-value confirmed the researcher's hypothesis that the social trust component within the rural community had been highly effective in achieving stable security.Hypothesis 3: The cohesion and solidarity of the local community has been very effective in achieving sustainable security.The observed ratio in the second group was much higher than the first group and the p-value supported the researcher's hypothesis that social cohesion and solidarity within the rural community had been highly effective in achieving sustainable security. Discussion of Results & ConclusionThe results of the present study indicated that participation capacities, both in terms of mental engagement (people's mindset towards participation, cooperative thinking, and collective will to solve problems) and objective aspects (including participation among villagers and in public/social activities), were at an upper level in the studied area. Regarding the social component, the local community perceived interpersonal trust, generalized trust, and institutional trust (mostly in non-official and non-governmental institutions) to be largely present. Similarly, social cohesion and solidarity (in-group and inter-group interactions and relations, as well as out-group relations) were evaluated at a high level. The findings of this research are consistent with the results obtained by previous studies, such as those conducted by Kladivo (2012), Geertrui et al. (2013), and Bazarafshan and Tulabinejad (2015). Based on the results, it is suggested that in addition to prioritizing native and local values and strengthening effective social institutions (e.g., Dispute Resolution Council), attention should be paid to people with social influence. Furthermore, the constructive interaction of official institutions (e.g., Islamic Council, Rural municipality) – which is currently less favored by the local community – should be addressed as a potential solution.